Evolution of DB white dwarfs in the Canuto and Mazzitelli theory of convection - Althaus, Leandro Gabriel (1996)
We compute the evolution of DB (helium-rich envelope) white dwarf models with masses between 0.4 and 1 Mo and metallicities of Z=O.OOI and 0.004, taking into account Canuto & Mazzitelli's new theory of convection. This theory, which has no free parameters and includes the full spectrum of turbulent eddies, has been successfully tested in different stellar objects and represents a substantial improvement compared with the classical mixing length theory used in most white dwarf studies. Using thermal time-scales we find that, for the range of masses and metallicities assumed in this study, the Canuto & Mazzitelli theory yields theoretical blue edges between 24 200 and 25 600 K, which is in good agreement with observations of pulsating DB white dwarfs. Calculations are performed considering the mixing length theory as well. In this context, our results are consistent with previous computations.